La Valorisation Des Ressources Forestières Au Niveau De La Wilaya De Saida - Meddah, Fadéla; Zatla, Najat (European Scientific Journal, ESJ, 2018)
The forestry economy tends to become a privileged way of development, making it possible to offer to the territories in mutation an alternative means of production. Algeria has been trying since 2008 (in accordance with the master plan for natural areas and protected areas) a forest policy that takes into account the multiple roles that the forest can play : protection, production and social promotion. This work aims to study the process of valorization of forest resources in territory of Saida. The process is based mainly on two advances : the exhaustive identification of resources and the development of valorization mode. These advances can not be maintained, unless, a territorial dynamic associating the actors of the sector of the forests and the actors of the territory, will be created. An entry by the territory, the resources and territorial development is privileged. This theoretical entry is illustrated by a comprehensive approach based on the analysis of stakeholder surveys and articulated with quantitative analysis. This analysis conclude that the territorial dynamics are absent at the level of the territory , which has led to an under-exploitation of resources.